On Products of Delta Distributions and Resultants - Bauer, Michel; Zuber, Jean-Bernard (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
We prove an identity in integral geometry, showing that if ₓ and ₓ are two polynomials, ∫dxδ(ₓ) ⊗ δ(ₓ) is proportional to δ() where is the resultant of ₓ and ₓ.